Development of Local History Learning with the Heroism Theme of K. Gholib Based on E-Book for Private Vocational School Students in Pringsewu Regency - Yoga Fernando Rizqi; Djono Djono; Susanto Susanto (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The purpose of this research is to discuss the development of material that supports the history of the struggle of K.H Gholib, who then compiles it into an e-book using the software "Flip PDF Professional 2.4.6.8". It was developed separately to analyze the material and increase student interest in Private Vocational High Schools in Pringsewu District by instilling the values of nationalism, heroism, and patriotism of a religious figure and fighter who participated in the struggle for independence in Lampung from the attack of the Dutch Military Aggression II in 1949. The research method used was the research and development of "R&D". The focus of e-book development uses the ADDIE development model through five intoxices, namely: analysis, design, development, implementation, and evaluation. The final results of this study show how the preparation and implementation of e-books in the classroom, so that the product developed can foster student interest in learning.